2009
DOI: 10.1386/jammr.2.1and2.113/1
|View full text |Cite
|
Sign up to set email alerts
|

A first for women in the kingdom: Arab/west representations of female trendsetters in Saudi Arabia

Abstract: Postcolonial and media literatures have documented the West's association with Muslim/Arab woman and images of passivity and oppression. The literature has yet to systematically consider western depictions of the Muslim Arab woman who is a trendsetter. How does the western press depict this powerful woman and do western and Arab media depict this woman similarly or differently? This article reports on a discourse analytical study of 32 articles that mention prominent Saudi women achieving positive firsts in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…On the other hand, this very fact may have prompted media discussion of women's participation in the labor force and the economy. A newspaper analysis of Arab and Western representations of female trendsetters in Saudi Arabia showed that “the largest single concentration of stories (27) in [a] sample of 214 stories was about Saudi businesswomen” (Kaufer and Al-Malki 2009, 115). Saudi female students also outnumber male students in the fields of business and economics (Buttorff, Al Lawati, and Welborne 2018, 71), which likely contributes to the high share of empowerment coverage that focuses on economics.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…On the other hand, this very fact may have prompted media discussion of women's participation in the labor force and the economy. A newspaper analysis of Arab and Western representations of female trendsetters in Saudi Arabia showed that “the largest single concentration of stories (27) in [a] sample of 214 stories was about Saudi businesswomen” (Kaufer and Al-Malki 2009, 115). Saudi female students also outnumber male students in the fields of business and economics (Buttorff, Al Lawati, and Welborne 2018, 71), which likely contributes to the high share of empowerment coverage that focuses on economics.…”
Section: Empirical Results and Discussionmentioning
confidence: 99%
“…Speakers have choices in the words they use and choose language to represent not only the world, as they understand it, but also in how they wish to construct it. 29 This link between linguistic behavior and worldview has important implications for our study. Controlling the terms of discussion-shaping discourse-is critical in persuasion and influence.…”
Section: Theory and Rationalementioning
confidence: 94%
“…A reasonable number of case studies describing women in the Middle East propose that women have a positive outlook toward religion's role in their lives, in that women do not feel constrained by Islam (Gallant and Pounder, 2008;Kaufer and Al-Malki, 2009;Al-Dajani and Marlow, 2010;Madichie and Gallant, 2012), as opposed to previous studies describing religion as an obstacle (Dechant and Al-Lamky, 2005;Redien-Collot et al, 2017). Similarly, researchers have recognized that the normative macro-level institutions (for example, women being prohibited from traveling or interacting with the opposite gender without a male chaperone) are not perceived as religious matters per se.…”
Section: Religion -Islam As An Ideological Frameworkmentioning
confidence: 99%